A numerical approach to the taxonomy of xanthomonas and some phytopathogenic pseudomonas spp. as determined by phenotypic properties and protein gel electrophoresis - Steyn, P.L. (University of Pretoria, 2022)
Thesis (PhD (Microbiology))--University of Pretoria, 1990.